Estilos de vida saludables: Actividad física en adolescentes tardíos de la Unidad Educativa Urcuquí - Cando Rodríguez, Fernanda Jazmín (2024)
This research addresses an important topic, focusing on the physical activity habits of late adolescents (ages 15-18) at the Unidad Educativa Urcuquí, located in the canton San Miguel de Urcuquí. The project is focused toward healthy lifestyles. This study employed a mixed-method approach, both qualitative and quantitative, using the Physical Activity Questionnaire for Adolescents (PAQ-A) as the instrument. This questionnaire has been translated into various versions for Latin America and was modified to suit the study's needs. It was used to analyze different aspects of physical activity performed by the adolescents, such as the type of physical activity and the frequency with which it is carried out. These parameters were specified over a seven-day period. The results revealed that although most students actively participate in physical education classes and show moderate interest in exercising during the week, only 1% meet the daily physical activity recommendations outlined by the World Health Organization. On weekends, there is a significant decline in physical activity, with 60% of students reporting little to no activity.